PATTERNS OF MEDICINE USE FOR COVID-19 PATIENTS AT UNDATA HOSPITAL PALU - Amelia Rumi; Nurul Ambianti; Desti Sulistiani Arbi (Universitas Airlangga, 2022)
Background: Covid-19 cases had drastically increased. Little therapy has been formulated to respond to the situation. Covid-19 symptoms in Indonesia are divided into four classes: asymptomatic, mild, moderate, and severe. Aims: This study aims to illustrate the pattern of drug use in Covid-19 patients at Undata Palu Hospital. Methods: This study is a type of cross-sectional descriptive study using a cross-sectional design and collecting data retrospectively from medical records at Undata Hospital Palu in 2020. Results: In 2020, 186 patients were confirmed positive for Covid-19. There were 95 female patients (51.9%) and 50 patients at the age of 46-55 years (27.3%). The severe symptoms happened to 109 patients (59.6%). The most common clinical manifestation was cough in 127 patients (23.3%). The most common comorbidity was pneumonia (30.8%). The most widely used primary therapy was the antibiotic azithromycin applied to 155 patients (30.0%), and the most widely used supportive therapy was vitamin C among 141 patients (20.1%). Oseltamivir antiviral therapy was administered to 132 patients (25.6%) and remdesivir to 34 patients (6.6%). Conclusion: Covid-19 patients were mostly treated with antibiotic therapy (41.5%), antiviral therapy (32.2%), antimalarial therapy (15.7%), and corticosteroid therapy (10.7%). As many as 132 patients took oseltamivir, and 34 patients took remdesivir. However, for now, oseltamivir is no longer used.